Anesthetic cream relieves pain after cryotherapy treatment of plantar and palmar warts. Issue 5 (8th July 2019) - Choi, Min Wha; Noh, Tai Kyung; Han, Tae Young; Lee, June Hyunkyung
Abstract: Cryotherapy using liquid nitrogen is an effective and commonly used treatment for palmoplantar warts. However, pain can be a limiting factor in the effective use of cryotherapy. In this study, we found that a single application of anesthetic cream following cryotherapy treatment of warts reduced posttreatment pain and led to improved tolerability of the procedure.